2016
DOI: 10.3389/fendo.2016.00121
|View full text |Cite
|
Sign up to set email alerts
|

A “Timed” Kiss Is Essential for Reproduction: Lessons from Mammalian Studies

Abstract: Reproduction is associated with the circadian system, primarily as a result of the connectivity between the biological clock in the suprachiasmatic nucleus (SCN) and reproduction-regulating brain regions, such as preoptic area (POA), anteroventral periventricular nucleus (AVPV), and arcuate nucleus (ARC). Networking of the central pacemaker to these hypothalamic brain regions is partly represented by close fiber appositions to specialized neurons, such as kisspeptin and gonadotropin-releasing hormone (GnRH) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 137 publications
0
12
0
1
Order By: Relevance
“…Accordingly, downregulation of GnIH expression by estrogen may be the mechanism of estrogen positive feedback to GnRH/LH release at least in female rodents [see Ref. (114, 115) for reviews].…”
Section: Control Of Gnih Expression and Mode Of Gnih Actionmentioning
confidence: 99%
“…Accordingly, downregulation of GnIH expression by estrogen may be the mechanism of estrogen positive feedback to GnRH/LH release at least in female rodents [see Ref. (114, 115) for reviews].…”
Section: Control Of Gnih Expression and Mode Of Gnih Actionmentioning
confidence: 99%
“…Kisspeptin neurons in the ARN, located on both sides of the third ventricle, develop at embryonic day 16.5 and become synaptically connected to GnRH neurons [5], unlike another kisspeptin population in the anteroventral periventricular nucleus (AVPV) detected at later developmental stages [6]. Kisspeptin neurons are thought to "time" reproduction by coordinating inputs for maturation and regulation of the GnRH pulse generator [7]. Loss-of-function mutations in Kiss1R cause the absence of sexual maturation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since these discoveries, the kisspeptin system has been considered as a major puberty gatekeeper and reproductive regulator, upstream of GnRH [for reviews see Ref. ( 15 17 )]. Nevertheless, Tang and collaborators ( 18 ) recently showed that gametogenesis and reproductive capability are not impaired in zebrafish mutant lines for Kiss, as well as for kisspeptin receptors (KissR), suggesting that the Kiss/KissR systems may be dispensable for the reproduction of some non-mammalian vertebrates.…”
Section: Introductionmentioning
confidence: 99%